PENGARUH PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN HASIL BELAJAR MATEMATIS SISWA - Metrilitna Br Sembiring (MES: Journal of Mathematics Education and Science, 2019)
Abstract. This study discusses the influence of the scientific approach to mathematical learning outcomes. The type of research used in this writing is quasi-experimental, with scientific approach data collection on students' mathematical learning outcomes. Data analysis used with Simple Regression Analysis Test. Based on the analysis obtained by the results of the study, namely: the relationship or correlation between learning approaches with student learning outcomes with regression , with . The values for testing the data can use the Anova table   and the significance level of 0.000 0.05. So that it can be said that the values of the two data are different. Thus, it can be concluded that there is the influence of the scientific approach to students' mathematical learning outcomes. This shows that the learning approach has a significant effect on students' mathematical learning outcomes. The coefficient of determination is   means that the contribution or influence of the santifik approach (X) on the students' mathematical learning outcomes (Y) is . Thus, the scientific approach is better at contributing to students' mathematical learning outcomes.Keywords: Scientific Approach, Learning Outcomes